Application of the Active Learning Model in Admin Panel Development as Application Development Support at PT Kinema Systrans Multimedia - Shifa, Andrian Dwi Nur; Ayuningsih, Ekatri (Edumaniora : Jurnal Pendidikan dan Humaniora, 2023)
This research aims to explore the application of the active learning model in admin panel development as an integral part of application development at PT Kinema Systrans Multimedia. In the rapidly developing digital era, developing applications is becoming increasingly important as a tool to support business operations. However, developing an admin panel, which is a user interface for managing and monitoring applications, requires an appropriate learning approach in order to achieve optimal results. In this research, we focus on the application of active learning models, which involve students directly in the learning process, to understand how this approach can influence the development of admin panels. Various active learning models such as problem-based learning, project-based learning, and cooperative learning will be explored in the context of information technology development. The research method used includes data collection through observation of the learning process, interaction between developers, and evaluation of the results resulting from the application of the active learning model. Qualitative analysis will be conducted to identify the benefits and challenges of implementing this learning approach in the context of admin panel development. It is hoped that the results of this research will provide valuable insight for PT Kinema Systrans Multimedia and the academic community about the importance of appropriate learning approaches in developing effective information technology. Thus, it is hoped that this research can become a basis for increasing the efficiency and effectiveness of admin panel development to support application development at PT Kinema Systrans Multimedia.